The Mishnaic mental revolution: a reassessment - Rozen-Tsevi, Yishai (The journal of Jewish studies, 2015)
The article argues that the self formed by the Mishna, authoritative collection of exegetical material embodying the oral tradition of Jewish law, is markedly different from the self defined as per Hellenistic philosophy. It mentions that innovative use the Mishnah makes of mental categories to determine legal outcomes that created a subjectivity which is related to the prominence that the inner self receives in Stoic philosophy.